2014
DOI: 10.1007/s00520-014-2534-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of cancer cachexia in patients with advanced non-small cell lung cancer

Abstract: CC presence and decreased skeletal muscle mass are associated with poor prognosis in advanced NSCLC patients receiving chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
152
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(164 citation statements)
references
References 21 publications
6
152
2
4
Order By: Relevance
“…After chemotherapy, men had a significantly higher decrease in muscle tissue than women, which was also seen by Kimura et al [7]. Regarding age, all adipose tissue compartments increased significantly more in younger than in older patients.…”
Section: Discussionsupporting
confidence: 76%
“…After chemotherapy, men had a significantly higher decrease in muscle tissue than women, which was also seen by Kimura et al [7]. Regarding age, all adipose tissue compartments increased significantly more in younger than in older patients.…”
Section: Discussionsupporting
confidence: 76%
“…Several studies have reported that skeletal muscle mass decreases in patients receiving chemotherapy [20,21,22]. Kimura et al [23] reported that cancer-related cachexia and decreased skeletal muscle mass are associated with a poor prognosis in patients undergoing chemotherapy. We were unable to investigate nutrition treatment and skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…(1-4) International consortia have thus identified early recognition of cancer cachexia as a critical goal, calling for interventions to be targeted early in the process rather than when end-stage wasting occurs. (5)…”
Section: Introductionmentioning
confidence: 99%